Optimalisasi Situs Web Pondok Pesantren Al Munawwir Yogyakarta Sebagai Media Edukasi Pencegahan dan Penanganan Covid-19 - Hasanah, Dian Uswatun; Alfi, Ahmad (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
The purpose of this study was to determine and analyze studies on the use of websites by the Al Munawwir Krapyak Islamic Boarding School in Yogyakarta in providing education and promotion on the prevention and handling of Covid-19, both within the pesantren and in communities outside the pesantren. This study uses a qualitative descriptive approach with content analysis method. The documents for which the data were analyzed were sourced from articles published on the official website of the Al Munawwir Krapyak Islamic Boarding School, Yogyakarta. The data collection technique in this research is document analysis. The validity of the data was in the form of theoretical triangulation with interactive (flowing) data analysis techniques. Interactive techniques include the stages of data reduction, data presentation, and drawing conclusions. The results of the research prove that the Al Munawwir Islamic Boarding School website www.almunawwir.com is influential in providing education about the prevention of Covid-19, education about health protocols in Islamic boarding schools, education about health protocol facility instruments in pesantren, and explaining sharia solutions to problems. worship in times of pandemic. In conclusion, the Pondok Al Munawwir Krapyak Yogyakarta website can be categorized as a good website because it is in accordance with the criteria for the value of a website, especially in education and promotion related to the prevention and handling of Covid-19. Keywords: Website, media, education, prevention and handling, Covid-19